48.4k views
5 votes
Solve by factoring 6x^3 - 16x^2 - 32x = 0. Enter your work

2 Answers

3 votes

Answer:

Explanation:

The common factor is 2x

2x(3x^2 - 8x - 16)

(x - 4)(3x+4)*2x = 0

x = 2

x = 4

x = -4/3

This does not graph too awfully well, but at least it givens you a notion of the roots.

Solve by factoring 6x^3 - 16x^2 - 32x = 0. Enter your work-example-1
User Doup
by
5.6k points
3 votes

Hey there! :)

Answer:

x = -4/3, 0, 4.

Explanation:

Starting with:

6x³ - 16x² - 32x = 0

Factor out the greatest common factor between each term, or 2x:

2x(3x² - 8x - 16) = 0

Factor the expression inside the parenthesis:

2x(3x +4)(x - 4) = 0

Use the Zero Product Property to solve the equation:

2x = 0

x = 0

---------

3x + 4 = 0

3x = -4

x = -4/3

-------------

x - 4 = 0

x = 4

-------------

Therefore, the solutions to this equation are:

x = -4/3, 0, 4.

User SeanVDH
by
6.5k points